The moment of seeing : Minor White at the California School of Fine Arts - Comer, Stephanie; Klochko, Deborah (San Francisco, Calif. : Chronicle Books, 2006)
Chronicles the history of the first fine-art photography department founded by Ansel Adams at the California School of Fine Arts--now known as the San Francisco Art Institute--in 1944, focusing on the contributions of director Minor White, who taught alongside Adams, and includes images by instructors as well as students of the program.
Includes bibliographical references.
Adult.
Adult
Keywords: White, Minor; White, Minor; California School of Fine Arts (San Francisco, Calif.); California School of Fine Arts (San Francisco, Calif.); Photography -- Study and teaching (Higher) -- California -- San Francisco; Photography -- San Francisco (Calif.) -- Study and teaching